Sensor network configuration under physical attacks. (9th April 2009) - Wang, Xun; Gu, Wenjun; Schosek, Kurt; Chellappan, Sriram; , Dong Xuan
Sensor networks will typically operate in hostile environments, where they are susceptible to physical attacks resulting in physical node destructions. In this paper, we study impacts of physical attacks on network configuration w.r.t. lifetime. While lifetime is constrained by limited energies and has been addressed before, they are not applicable under physical attacks. In this paper, we define a practical sensor network lifetime problem under physical attacks. We then analytically determine the minimum number and sensor deployment plan to meet lifetime requirement under physical attacks. We make several important observations, including the high sensitivity of lifetime to physical attacks.